Representation of Madrid and Barcelona in Films During the Spanish Transition - Codesido, Váleri; García García, Francisco; García Guardia, María Luisa (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
As a reflection of the imminent change from late Francoism to the Spanish transition, discourses emerged in film narratives which portrayed aspects of society practically unaddressed until then, such as the LGTBIQ+ content, the “quinqui” marginality or the `S´ cinema. Madrid and Barcelona are presented as the main settings for new discursive constructs that portray a generation which differed from the preceding Francoist modes. This research analyses and exposes the synergy between characters and urban settings by which the city acts as an emotional map of the story and a location for change in the first films of Spanish democracy.